Slowing the time-fluctuating MIMO channel by beam forming. - Chizhik, D.
It has been reported that the number of transmitters that can be used beneficially in a multiple-input multiple-output (MIMO) system is limited by the coherence time of the channel due to difficulties with channel estimation at the receiver. Furthermore, rapid channel fluctuations degrade the performance of feedback schemes that would otherwise increase the information throughput that may be achieved. These impediments either reduce achievable capacity or impose an effective "speed limit" on the mobile, above which the effective throughput is reduced. In this paper, the signal incident at the mobile is represented as a sum of plane waves. The channel transfer matrix is found to factor into time-dependent and time-independent parts. A processing method is proposed whereby the received signals are first preprocessed so as to produce signals that fluctuate on a much slower time scale. The preprocessing consists of beam forming, followed by Doppler compensation for signals received on each beam. Both operations are nonsingular and do not alter the capacity of the MIMO channel. Beam forming effectively partitions the angular spectrum at the mobile, with each partition suffering a smaller Doppler spread, resulting in a "slowed down" channel fluctuation due to mobile motion. The coherence time of the preprocessed channel is found to increase by a factor on the order of the number of mobile receive antennas. In the limit of an infinite number of mobile receive antennas, the MIMO channel is shown to become static. These results remove constraints imposed by training requirements on the number of transmit antennas and increase allowed vehicle speeds. The "slowed down" channel characteristics may also be fed back to the transmitter, allowing an increase in information throughput.
Keywords: Doppler compensation; Beam forming; Channel coherence time; Channel estimation; Channel transfer matrix; Feedback scheme; Mobile receiver antennas; Multiple input multiple output system; Receiver; Time-fluctuating MIMO channel; Transmit antennas; Transmitters